Agroecological crop protection (Springer, 2017)
This book is devoted to Agroecological Crop Protection, which is the declension of the principles of agroecology to crop protection. It presents the concepts of this innovative approach, case studies and lessons and generic keys for agroecological transition. The book is intended for a wide audience, including scientists, experimenters, teachers, farmers, students. It represents a new tool, proposing concrete keys of action on the basis of feedbacks validated scientifically. Beyond the examples presented, it is therefore of general scope and proposes recommendations for all temperate and tropical cropping systems. It contributes to the training and teaching modules in this field and it is an updated information support for professionals and a teaching aid for students (agronomy, crop protection, biodiversity management, agroecology).